Anthropometric Study of Facial Index and its Clinical Implications among Medical Students in Devdaha Medical College and Research Institute, Rupandehi, Nepal - Yadav, Sanjay Kumar; Chaudhary, Deepak; Pandey, Niraj (Medical Journal of Eastern Nepal, 2023)
Background: The human facial contour has always been an interesting subject for anatomists, anthropologists, plastic surgeons and artists. The purpose of study was to create and evaluate data on face anthropometry. Methods: A descriptive cross-sectional study was conducted in 200 medical students studying at a tertiary care hospital during the period of 5th September 2022 to 5th February 2023 after ethical clearance from the institutional review committee (Ref. No: 194/079/080). Simple random sampling was done. Data were collected, entered in Statistical Package for Social Sciences version 20. Results: We observed that mean indices of the facial height was10.43± 0.84, facial width was 12.40±0.68,range of facial height was 9.31-13.01 and range of facial width was11.10-15.13 cm. Mesoprosopic face was predominant among female whereas leptoprosopic face type was more common among male population of the study. The most common face type was mesoprosopic and the uncommon was hyperleptoprosopic. The least common face among men was Europrosopic while among women was hyperleptoprosopic type. There was significant difference in the male and the female facial index. Conclusions: A higher index for all the parameters was seen among males than females. The data obtained may be useful in anthropological research, forensic, genetic research, as well as in medical clinical practice.